2015
DOI: 10.1596/1813-9450-7442
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of China's Slowdown on the Asia Pacific Region: An Application of the GVAR Model

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
(28 reference statements)
1
24
0
Order By: Relevance
“…This evidence for the Republic of Korea may shed light on a finding of Inoue, Kaya, and Ohshige (2015). Using a Global Vector Autoregressive model and quarterly data over the period covering the first quarter (Q1) of 1979 until Q3 2014, they reported that a 1% negative PRC GDP shock would only reduce the Republic of Korea's GDP by 0.07%.…”
Section: Resultsmentioning
confidence: 91%
“…This evidence for the Republic of Korea may shed light on a finding of Inoue, Kaya, and Ohshige (2015). Using a Global Vector Autoregressive model and quarterly data over the period covering the first quarter (Q1) of 1979 until Q3 2014, they reported that a 1% negative PRC GDP shock would only reduce the Republic of Korea's GDP by 0.07%.…”
Section: Resultsmentioning
confidence: 91%
“…Ahuja and Myrvoda (2012), or global vector autoregressive (GVAR) models, e.g. Dizioli et al (2016), Dreger and Zhang (2013), Hong et al (2016), Cesa-Bianchi et al (2011), Cashin et al (2016), or Inoue et al (2015 (see Table 1). Most of these models include variables such as real GDP growth, inflation, real exchange rates, and short-and long-term interest rates.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…Employing the global vector autoregressive model and using a dataset through the third quarter of 2014 for 33 countries, Inoue et al (2015) find that a negative Chinese GDP shock adversely affects export-dependent members of the East Asian product value chain, such as Japan, Malaysia, Singapore and Thailand, as well as commodity exporters, such as Indonesia.…”
Section: Introductionmentioning
confidence: 99%